2008
DOI: 10.1186/1471-2229-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA regulation of ovule development in the cotton plant, G. hirsutum L

Abstract: Background: The involvement of small RNAs in cotton fiber development is under explored. The objective of this work was to directly clone, annotate, and analyze small RNAs of developing ovules to reveal the candidate small interfering RNA/microRNAs involved in cotton ovule and fiber development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…Further, we previously observed that photomorphogenesis-related factors (for example, PHYC, SPA1, FAR1, COP1, COP9, CIP7, CIP8 and RTP2) were targeted by putative ovule-derived short interfering RNAs during the initiation and elongation phases of fibre development 28 , thus indirectly supporting a role for light signalling in fibre traits. Our data suggested that some fibre traits (for example, ELO and STR) might be minimally affected by somaclonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we previously observed that photomorphogenesis-related factors (for example, PHYC, SPA1, FAR1, COP1, COP9, CIP7, CIP8 and RTP2) were targeted by putative ovule-derived short interfering RNAs during the initiation and elongation phases of fibre development 28 , thus indirectly supporting a role for light signalling in fibre traits. Our data suggested that some fibre traits (for example, ELO and STR) might be minimally affected by somaclonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated cotton miRNAs and their regulatory functions in developmental processes of cotton fibers [6][7][8][9][10]. Especially, the high throughput RNA-sequence technology was employed to identify 562 candidate miRNAs from 7-DPA fibers of allotetraploid cotton [9], while cotton DD-genome shotgun sequences were examined to annotate 348 miRNA candidate sequences [2].…”
mentioning
confidence: 99%
“…They identified three plant microRNAs (miR172, miR390, and ath-miR853-like) and demonstrated dpa-specific small RNA expression profiles during ovule development. These result suggested the complex dpa-specific small RNA regulation in ovule development covering 0-10 dpa fiber development stages [97].…”
Section: Small Rna-mediated Gene Regulation Studies In Cottonmentioning
confidence: 82%
“…Although the regulatory mechanisms of microRNAs and small non-coding RNAs were determined in overall plant growth and development [96], their specific role in the regulation of fiber cell elongation and developmental processes were more widely elucidated primarily after 2008. The roles of small interfering and microRNAs in the development of the cotton ovule and fiber elongation were annotated by Abdurakhmonov and his colleagues [97], as a first attempt in fiber genomics. They identified three plant microRNAs (miR172, miR390, and ath-miR853-like) and demonstrated dpa-specific small RNA expression profiles during ovule development.…”
Section: Small Rna-mediated Gene Regulation Studies In Cottonmentioning
confidence: 99%